Manajemen Outbound Taman Wisata Matahari Di Cisarua Kabupaten Bogor tahun 2020 (Indonesian Journal for Physical Education and Sport, 2022)
Wiwi Safitri. 2021. Management Analysis of Outbound Activity in Matahari Tourism Park Cisarua Bogor 2020. Skripsi, Department of Health and Recreation Physical Education / S1 Faculty of Sport Science, State University of Semarang. Advisor Aris Mulyono, S, Pd., M, Pd.Keywords: Management, Outbound,Taman Wisata Matahari Recently, the enthusiasm of the community, organizations and companies has been busy organizing recreational activities together as an effort to improve the performance and performance of their members or employees. One of them is an activity in the form of Outbound training. The development of the sports industry is currently very much in demand by private entrepreneurs, especially outbound. This Matahari Tourism Park is one of the tours with a concept of carrying outbound activities as a concept of recreation and education for the community. The problem of this research is how to implement the management function in the management of Taman Wisata Matahari in the presence of the same business competition in other places. Manager's leadership, outbound trainers and visitors. Data analysis uses focus data selection to answer the problem formulation (data reduction), which is arranged briefly (display data), and develops after being in the field (verification). The results showed that the planning function of the solar tourism park has its own vision and mission of the company which plans are long-term and short-term. Taman Wisata Matahari has an organizing line (leadership, staff, functional). The process of recruiting employees is always prioritized to support good and efficient organizational activities. The existence of good promotions, welfare, warning letters (SP) to dismissal if they do not comply with all existing regulations and retired employees who are always carried out by the Taman Wisata Matahari. Motivation for employees is carried out by HRD leaders to improve employee performance. Evaluating activities and employees is always the main thing to assess the performance of the system. Based on the above results it can be concluded that the management (planning, organizing, employees, motivation and supervision) at Taman Wisata Matahari has good and neat management. Management needs to carry out intensive supervision both in the office and in the field, this is to reduce the occurrence of errors in management implementation